STRATEGI INDONESIA MENGGUNAKAN RUMAH BUDAYA SEBAGAI SARANA DIPLOMASI KEBUDAYAAN TERHADAP JERMAN - Yuza, Bertha Pramesti; Jamaan, Ahmad (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2016)
This paper aims to analyze about the Indonesian strategic to use Rumah Budaya as instruments of cultural diplomacy in Germany. Rumah budaya is primary tools to strengthening the relationship between two countries and as an information center Indonesian culture toward germany. The result of this research show that the influential Rumah Budaya of the positive image of Indonesia and the increasing number of tourists to Indonesia. They are the most people who like traveling, furthermore Germany are the largest income source for the international tourism industry in Indonesian.Keyword :culture diplomacy, Rumah Budaya Indonesia, soft power